Taking Advantage of Indonesia's Demographic Bonus in 2024: Challenges and Opportunities (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Demographic bonus is a phenomenon when most of a country's population is in the productive age group, which can provide high potential for economic growth. 2020-2030 will be an important year for many countries as some of them will experience the peak of their demographic dividend. However, the opportunities and challenges associated with this situation need to be studied in depth so that the maximum potential of the demographic bonus can be utilized. This study aims to analyze the challenges and opportunities faced by Indonesia, which is facing a demographic bonus era. This research uses a qualitative approach with descriptive methods. The results of the study show that the demographic bonus is a golden opportunity for Indonesia to increase economic growth and people's welfare. With the population of productive age being larger than the non-productive age population, there is great potential to increase total output and production in various economic sectors. However, in order to take advantage of the demographic bonus effectively, it is necessary to make efforts to build quality human resources through improving the quality of education and job training. In addition, the labor market must be able to absorb an abundant workforce so that the unemployment rate can be minimized. The importance of digital transformation and the industrial revolution is also a focus in efforts to face the challenges of technological development. With support from the government, the private sector and the community, Indonesia has great potential to take advantage of the demographic bonus as a driver of sustainable economic growth and improve the welfare of society at large.
Keywords: Demographic Bonus; Population; Welfare; Productive Labor; dependency ratio